AMSS Thirty-second Annual Conference: Bloomington, IN - September 26-28, 2003 (American Journal of Islam and Society, 2003)
The Thirty-second Annual AMSS Conference, cosponsored this year byIndiana University's Middle Eastern and Islamic Studies program and thedepartment of Near Eastern Languages and Cultures, analyzed "EastMeets West: Understanding the Muslim Presence in Europe and NorthAmerica." Katherine Bullock (program committee chair, University ofToronto), Nazif Shahrani (professor of anthropology, director of MiddleEastern and Islamic studies program, Indiana University), PatrickO'Meara (dean, International Programs, Indiana University), and LouaySafi (president, AMSS) welcomed attendees and made introductoryremarks.Since the passing of Edward Said coincided with the beginning of theconference, in his welcoming remarks Shahrani referred to this greatscholar's lasting legacy. In fact, many panelists during the course of theconference talked about the importance of Said's research to their ownwork.Regular AMSS attendees such as myself would tell you that this conferencewas a tightly organized orchestra of excellent sessions, one after theother. The number of sessions was smaller than usual, and there were fewerparallel sessions, probably because far more academic rigor had been exercisedin selectiong papers than had been the case in previous conferences.A special delight on the first day was the lunch and jumu'ah prayer atthe Bloomington Islamic Center, catered and served by BloomingtonMuslim community volunteers. After these events, the conference beganin earnest. The opening panel, "A Political Philosophical Perspective onIslam and Democracy," featured M. A. Muqtedar Khan (Adrian College),who addressed the theoretical aspects of this debate, and Nazia Khandwalla(University of Texas), who looked at the debate in an empiricalstudy of slum-dwelling women in Karachi ...